Virtual reality and 3D printing in head and neck cancer: an educational experience - Ferretti, Fabrizio; Nonis, Francesca; Novaresio, Andrea; Panico, Enrica; Zavattero, Emanuele; Borbon, Claudia; Moos, Sandro; Vezzetti, Enrico; Fasolis, Massimo; Ramieri, Guglielmo (Frontiers in Oncology, 2026)
BackgroundIn recent years, the growing adoption of Virtual Reality (VR) and 3D printing technologies has revolutionized surgical training by providing innovative opportunities for hands-on education. This study investigates the combined use of VR and 3D printed personalized anatomical models and cutting guides within the field of oral and maxillofacial oncologic surgery.Materials and methods: A mandibular tumour case was developed using the proposed approach, integrating both virtual and physical tools. Feedback was gathered from twelve surgical residents regarding their understanding of the case, the effectiveness of the immersive and three-dimensional technologies, and their overall satisfaction with the training experience.ResultsParticipants reported enhanced comprehension of complex surgical scenarios and valued the practical utility of the VR simulator combined with 3D printed models. The immersive environment facilitated skill acquisition in a risk-free setting.ConclusionThe findings underscore the significant added value of integrating VR and 3D printing technologies in surgical training, preparation, and simulation. This approach offers a safe, effective training platform that improves readiness for complex procedures in oncologic surgery and has the potential to be extended to other branches of maxillofacial surgery.